Laccase-Induced Gelation of Sugar Beet Pectin–Curcumin Nanocomplexes Enhanced by Genipin Crosslinking - Jia-Wei Lin; Gui-Li Jiang; Cui-Xin Liang; Ye-Meng Li; Xing-Yi Chen; Xiao-Tong Zhang; Zhong-Sheng Tang (Foods, 2023)
Research on the use of polysaccharides as hydrophobic bioactive carriers instead of proteins is still scarce. Sugar beet pectin (SBP) contains a small amount of protein and is a potential carrier for loading curcumin. In this work, SBP encapsulation, genipin crosslinking, and laccase-induced gelation were used to develop novel jelly food and improve the stability of curcumin without the incorporation of oil. By mixing the SBP solution (40 mg/mL) with curcumin powder (25 mg/mL SBP solution), an SBP–curcumin complex (SBP–Cur) was fabricated with a loading amount of 32 mg/g SBP, and the solubility of curcumin improved 116,000-fold. Fluorescence spectroscopy revealed that hydrophobic interactions drove the complexation of curcumin and SBP. Crosslinked by genipin (10 mM), SBP–Cur showed a dark blue color, and the gel strength of laccase-catalyzed gels was enhanced. Heating and UV radiation tests suggested that the genipin crosslinking and gelation strategies substantially improved the stability of curcumin. Because of the unique UV-blocking capacity of blue pigment, crosslinked samples retained 20% more curcumin than control samples. With the enhanced stability of curcumin, the crosslinked SBP–curcumin complexes could be a functional food ingredient used in functional drinks, baked food, and jelly food.